2020
DOI: 10.31557/apjcp.2020.21.4.1045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin in Comparison with Trichostatin A on the Reactivation of Estrogen Receptor Alpha gene Expression, Cell Growth Inhibition and Apoptosis Induction in Hepatocellular Carcinoma Hepa 1-6 Cell lLine

Abstract: in the promoter region of TSGs (Yang et al., 2017). Abnormal regional hypermethylation of the 5′ region of several TSGs has been observed in HCC (Baylin et al., 2011). Down-regulation of a variety of TSGs expression because of abnormal hypermethylation in their promoter regions could play a critical role in liver tumorigenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…In this experiment, We did not perform western blot in order to evaluate of HDAC1 and HDAC2 expression and also the acetylation status of histone H3 and a-tubulin but we decide to perform them in the next work. Previously, we evaluated the effect of GE and VPA on the other HCC cell lines including PLC/PRF5 and HepG 2 (Sanaei et al, 2017a;Kavoosi et al, 2016;Sanaei et al, 2017b). Thus, our studies provide a new avenue for cancer treatment through demethylating agents combined with histone deacethylase inhibitors.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this experiment, We did not perform western blot in order to evaluate of HDAC1 and HDAC2 expression and also the acetylation status of histone H3 and a-tubulin but we decide to perform them in the next work. Previously, we evaluated the effect of GE and VPA on the other HCC cell lines including PLC/PRF5 and HepG 2 (Sanaei et al, 2017a;Kavoosi et al, 2016;Sanaei et al, 2017b). Thus, our studies provide a new avenue for cancer treatment through demethylating agents combined with histone deacethylase inhibitors.…”
Section: Discussionmentioning
confidence: 87%
“…Our previous studies clearly show that genistein has a significant inhibitory effect on the growth of hepatocellular carcinoma HepG2 cell lines and induces apoptosis in these cell line with a time-dependent manner (Sanaei et al, 2017a;Sanaei et al, 2017b).…”
Section: Effect Of Dna Methyltransferase In Comparison To and In Combmentioning
confidence: 89%
“…Sanaei et al found that DNA demethylating agents such as genistein and histone deacetylase inhibitors (HDACIs) such as trichostatin A (TSA) may strongly reactivate silenced genes, enhance estrogen receptor alpha (ERα) reactivation and induction of apoptosis. These results may provide new avenues and therapeutic strategies for cancer therapy [48].…”
Section: Phytoestrogens and Nafld Related Hepatocellular Carcinoma (Hcc)mentioning
confidence: 89%
“…Additionally, they conducted a study examining the efficacy of curcumin compared to TSA in the reactivation of ERa. They showed that both drugs can induce apoptosis and inhibit cell growth via reactivation of ERa [ 76 ].…”
Section: Hdacis As Anti-cancer Agents In Hccmentioning
confidence: 99%